Direct bioconversion of rice residue from canteen waste into lipids by new amylolytic oleaginous yeast Sporidiobolus pararoseus KX709872. Issue 4 (21st April 2018) - Chaiyaso, Thanongsak; Srisuwan, Wimada; Techapun, Charin; Watanabe, Masanori; Takenaka, Shinji
ABSTRACT: The new amylolytic oleaginous red yeast, Sporidiobolus pararoseus KX709872, produced both α-amylase (540 ± 0.09 mU/mL) and amyloglucosidase (23 ± 0.00 mU/mL) and showed good ability to directly convert rice residue from canteen waste to biomass and lipids. Effects of medium composition and cultivation conditions on growth and lipid accumulation for strain KX709872 were investigated under shaking flask and upscaling levels. At C : N ratio of 25 : 1, pH 5.45, 22.36°C, and 199.40 rpm for 7 days, volumetric production of biomass and lipids, lipid content, and lipid productivity reached 17.69 ± 0.44, 8.35 ± 0.19 g/L, 49.48 ± 0.41% (w/w), and 1.67 ± 0.11 g/L/day, respectively. Production of lipids was also implemented in 5.0-L stirred tank bioreactor with 2.5 L of optimized medium at 300 rpm and 3.0 vvm for 5 days. Volumetric production of biomass and lipids, lipid content, and lipid productivity were 16.33 ± 0.49, 8.75 ± 0.13 g/L, 56.61 ± 0.04% (w/w), and 2.19 ± 0.03 g/L/day, respectively. Meanwhile, the fatty acids of lipids from strain KX709872 had high oleic acid content (60−62%) which was similar to those of vegetable oils, indicating that these lipids are promising as an alternative biodiesel feedstock. Moreover, the biodiesel derived from lipids of strain KX709872 had properties satisfying the criteria of ASTM D6751 and EN 14214 standards.